Assessing Management Involvement In Safety Issues: The Case Of The Metal Products Industry In Iran - Ooshaksaraie, Maryam; Azadehdel, Mohammad Reza (Asian Academy of Management (AAM), 2013)
The concept of management involvement in safety refers to the extent to which top- and middle-level managers become personally involved in critical safety activities within the organisation. Occupational accidents and incidents are symptoms of low management involvement in safety issues because most accidents could be prevented. The main objectives of this study were to evaluate management involvement in safety issues (such as safety values, occupational safety management, and employee well-being) and to analyse differences in management involvement in the metal products industry in Guilan Province, Iran, with regard to company size. A total of 714 respondents from 14 companies participated in the survey. The results showed that management involvement in safety issues was not strong in the metal products industry in Guilan Province. A oneway ANOVA analysis was applied to understand employees' perspectives on management involvement in safety. The results revealed that there was a significant difference regarding management involvement in safety with respect to company size. Large companies had stronger management involvement in safety compared to smaller companies